Green university initiatives in China: a case of Tsinghua University. Issue 4 (6th July 2015) - Zhao, Wanxia; Zou, Yonghua
Abstract : Purpose: – The purpose of this paper is to examine green university initiatives in the context of China, using Tsinghua University, which is China's green university pioneer, as a case study. Design/methodology/approach: – The research method used for this paper is a case study based on participant observation and document analysis. The approach to data collection includes the examination of archive records, yearbooks and statistical information regarding Tsinghua University. Findings: – This paper finds that Tsinghua's green university initiative is a response to Tsinghua's strategy of establishing a word-class university, with a goal of bearing more responsibility in promoting a sustainable society. Tsinghua employs one principle (green university) and three dimensions (green education, green research and green campus) to frame its green university initiative. Tsinghua's green university initiative has earned many achievements, but it has also faced many challenges, such as ignoring social justice, fragmented coordination efforts and the lack of effective communication and assessment mechanisms. Practical implications: – As a leading university and the pioneering green university in the country, Tsinghua University is very influential with regard to the development of green universities in China. Many other universities have designed their own programs based on Tsinghua's experiences in the green university initiative. As such, Tsinghua's experiences provide reference values to other universities in China. Originality/value: – This paper comprehensively examines the evolution, framework, achievements and challenges of the green university initiative of Tsinghua University. It helps the audience to know how China's universities understand and practice education for sustainable development.